Het Labourprogramma 1959 - Noppen, Herman; Fayat, Henri (Antwerpen : Ontwikkeling, 1959)
Vrijzinnige werkmansbibliotheek
Bibliotheek Camille Huysmans
Nederlands
Brochure
Keywords: Labour Party (Verenigd Koninkrijk).